Pengaruh Perubahan Iklim Terhadap Pertumbuhan Berbagai Jenis Tumbuhan; Bunga Kertas (Bougenvillea Glabra), Tasbih (Canna Indica), Glodokan Tiang (P. Longifolia), Pucuk Merah (S. Myrtifolium) Dan Lamtoro (Leulamtoro Leucocephala). Di Wilayah Kota Medan Sum - Faisal, Muhammad; Fadilla, Audia; Nurlita , Desi; Amirah , Nurul; Khairunnisa, Riska (CV. ITTC INDONESIA, 2024)
Climate change refers to changes in the pattern and intensity of climate elements over a specific period, typically compared to a 30-year average. These changes can include shifts in average weather conditions or changes in the distribution of weather events. This research was conducted around Jl. Pancing, Medan, North Sumatra, on December 6, 2024, with the aim of analyzing the impact of climate change on the growth of various plant species in urban areas. The research method used is quantitative descriptive. The results show that some plants in the area demonstrate a good ability to adapt to fluctuating temperature, rainfall, and light intensity. Plants such as leucaena, Canna indica, Monoon longifolium, and Bougainvillea glabra exhibit adaptation mechanisms in terms of morphology, physiology, and ecology, enabling them to survive and grow under changing weather conditions due to climate change.